Bible and Youth Catechism/2 Come and See: The Depth of Scriptural Wisdom Offered to Youth - Ciarocchi, Valerio (Paedagogia Christiana, 2025)
This contribution explores the biblical dimension of Youth Catechism/2 Come and See, highlighting its spiritual, historical, and cultural richness, being elements that permeate every page of the Bible. The Bible has always shaped the life and mission of the Church, a truth that cannot be emphasized enough, given its depth and beauty. Following an introduction that lays the groundwork for the discussion, we will examine the Magisterium’s contribution through two key documents, both addressing biblical and catechetical themes. We will analyze their insights and consider what original contributions can be made regarding the biblical dimension of catechesis, particularly for young people today. The study will conclude with a reflection on the work undertaken.